The role of the posterior malleolus in the treatment of unstable upper ankle joint injuries - A biomechanical study. Issue 7 (October 2022) - Kohler, F.C.; Schenk, P.; Koehler, P.; Hofmann, G.O.; Biedermann, U.; Wildemann, B.; Graul, I.; Hallbauer, J.
Abstract: Background: This biomechanical study aimed to test if the fixation of the posterior malleolus (PM) only with screws inserted from posterior to anterior (PA) restores stability comparable with the natural condition. The extent of stability was also compared with that of anterior to posterior (AP) screw osteosynthesis (OS) with an additional syndesmotic screw (SS). Methods: First, the stability of the upper ankle joint in seven pairs of intact lower legs were examined. Subsequently, half of the lower legs were treated with PA screw fixation of a PM fracture without SS and the other half with AP screw fixation with additional tricortical SS. Results: PA OS without SS showed significantly more diastasis (p = 0.027). The AP OS with an SS revealed a diastasis that was comparable with the intact condition (p = 0.797). The use of SS led to significantly higher stability compared to OS without SS (p = 0.019). Conclusions: The Fixation of the PM alone without an additional syndesmotic screw cannot achieve intact upper ankle stability. Fixation of a PM fracture with an SS helps in nearly achieving the natural condition.